Application of enzymes in drug discovery research: A Review - Akram, Muhammad; Syed, Sadat Ali; K, Narayana; M, Shilpa; Zainab, Rida; Khalil, Muhammad Talha; Zafar, Sadia (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Enzymes have effectively substituted many conventional chemical catalysts-reliant pharmaceutical drug manufacturing procedures. From this v-prospect, the use of enzymes in drug discovery research is quite encouraging. Numerous enzymes have been demonstrated to perform detoxification at the cellular level, for instance, the antioxidant enzymes, catalase, and superoxide dismutase (SOD). These enzymes work simultaneously to neutralize oxygen-free radical species. The enzyme-mediated pharmaceutical procedures include the synthesis of diverse semi-artificial antibiotics, dynamic enantiomers of medicines through kinetic determination, production of enantiomerically unadulterated types of amino acids, and others. Enzymes are being used to treat cancer and infectious disorders where antibiotics are no longer effective because of antibiotic resistance. Thus, the present article aims to review the diverse use of enzymes in the drug industries and discuss the features of enzymes that make them suitable drug candidates.